Transformasi Tata Kelola Pemerintahan Desa Menuju Smart Village Melalui Digitalisasi Layanan Administrasi - Darmawan, Prasojo Ashar Nur; Millatus Sholihah; Ning Mukti Indrayani (Idarotuna : Journal of Administrative Science, 2025)
The transformation of village governance has become an urgent necessity in the digital era. The digitalization of administrative services serves as a strategic step in realizing the concept of a Smart Village, namely a village capable of optimizing information technology to enhance public services, transparency, and community participation. This study aims to analyze the transformation process of governance in Kebonsari Village, Yosowilangun District, Lumajang Regency, towards a Smart Village through the implementation of digitalized administrative services. The research employs a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings indicate that the digitalization of village administration has improved service efficiency, accelerated the issuance of official documents, and facilitated public access to information. However, challenges remain in terms of human resources and digital infrastructure. In conclusion, the digitalization of administrative services constitutes a crucial foundation for the transformation of village governance toward a Smart Village, with key prerequisites including the enhancement of village officials’ competencies and adequate technological support.